2022
DOI: 10.3389/fdgth.2022.866119
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality for Distraction and Relaxation in a Pediatric Hospital Setting: An Interventional Study With a Mixed-Methods Design

Abstract: Accumulating evidence supports the use of virtual reality (VR) as an effective pain and anxiety management tool for pediatric patients during specific medical procedures in dedicated patient groups. However, VR is still not widely adopted in everyday clinical practice. Feasibility and acceptability measures of clinicians' experiences are often missing in studies, thereby omitting an important stakeholder in VR use in a clinical setting. Therefore, the aim of this mixed-methods study was to investigate the feas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Moreover, in their study, Bernaerts at al. [91] indicated the positive effect of a VR application on reducing stress and anxiety in a clinical pediatric hospital, comprising among others breathing exercises and minigames with interactive animations and objects. In recent years the development and implementation of serious game-biofeedback applications to promote self-management and mental well-being has been growing [92,93] and may be the future in VR interventions for stress management.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in their study, Bernaerts at al. [91] indicated the positive effect of a VR application on reducing stress and anxiety in a clinical pediatric hospital, comprising among others breathing exercises and minigames with interactive animations and objects. In recent years the development and implementation of serious game-biofeedback applications to promote self-management and mental well-being has been growing [92,93] and may be the future in VR interventions for stress management.…”
Section: Discussionmentioning
confidence: 99%
“…It was also noted that using VR helped improve the facilitation of health practitioners' tasks. Children would be less tense and fidgety during procedures and less resistant to proposed procedures (40,52,53).…”
Section: Virtual Reality To Reduce Pediatric Preoperative Anxietymentioning
confidence: 99%
“… 16 Studies have shown that new technologies, such as virtual reality, can be an effective tool for pediatric hospital settings compared to standard care; however, they are still not frequently used in routine practice. 17 …”
Section: Introductionmentioning
confidence: 99%